IS THERE ANY IMPROVEMENT IN EFFICACY OF EXTRACORPOREAL SHOCKWAVE LITHOTRIPSY THERAPY FOR TREATING RENAL STONES WITH INVENT OF NEW SHOCKWAVE MACHINES? - Sohail, Nadeem; Albodour, Amjad; Abdelraham, Khalid Mohammed (Journal of Ayub Medical College Abbottabad, 2019)
Background: Renal stone disease is a very common medical problem in general population. As with invent of newer therapeutic modalities, ESWL is already losing its popularity. But we believe it as an effective way of treating renal stones. This study was conducted to evaluate any improvement in success rate of ESWL therapy for treating renal stones with latest shockwave lithotripsy machines. Methods: Study conducted from June 2016 until November 2017 in Alkhor hospital, Hamad Medical Corporation, Qatar. All patients undergoing ESWL for renal stones in mentioned period were included. Total 197 patients underwent ESWL using newer machines. Factors already studied to affect the success rate like stone size, location, consistency (measured by Hounsfield units on CT), presence of stent were taken in consideration. After a period of 3 months either complete stone clearance or stone fragments smaller than 4 mm were considered as a treatment success. These results were compared to the results from literature. Results: Patients were followed until 3 months after treatment. 170 patients (86.29%) had complete stone clearance. Eleven patients (5.58%) had residual stone less than 4 mm, thus achieving an overall success of 181 patients (91.88%). 42 patients (21.32%) needed repeat session of ESWL with a maximum number of 3 sessions. 16 patient's (8.12%) required auxiliary procedures like flexible ureteroscopy. Post-ESWL complications were recorded in 12 patients (6.09%). Success rate was affected mainly by stone size with negligible effect of stone location. Presence of stent affected the number of sessions but has no impact on stone clearance. Conclusion: Although the stone size and to a negligible extent, the stone location and presence of stent may affect the stone clearance, nevertheless a significant improvement in success rate has been observed by use of new shockwave lithotripsy machines. Keywords: Kidney; extracorporeal shockwave lithotripsy; stone